2021
DOI: 10.1021/acssuschemeng.0c07409
|View full text |Cite
|
Sign up to set email alerts
|

Selective Extraction of Gold by Niacin

Abstract: Gold recovery using a sustainable and inexpensive method has tremendous environmental and economic implications. We developed a highly cost-effective and sustainable method of gold extraction in which aqueous Au3+ is precipitated selectively as it is complex with the biomolecule niacin, having an overall formula, [AuCl4]−[2Niacin + H]+, abbreviated as I. This selective precipitation occurs from mixtures of Au3+ with Ni2+, Cu2+, and Zn2+ along with commonly occurring alkali (Na+/K+) and alkaline earth (Mg2+/Ca2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 39 publications
(55 reference statements)
0
17
0
Order By: Relevance
“…In comparison to the reported novel gold adsorbents, though some showed reductive adsorption, other physi-and chemi-sorptions were also significant. That is, gold extracted by these adsorbents was a mixture of ionic and metallic gold 4,[12][13][14][15]19,[27][28][29] , therefore, it would require energy-and cost-intensive post-processing, for example, elution and precipitation to desorb and reduce the ionic gold, so that a full adsorption capacity can be achieved 30,31 . In contrast, as >95% extracted Au ions were reduced to metallic gold by rGO, it allowed direct isolation of metallic gold from rGO surface without further post-adsorption processing, providing an extra advantage of rGO for gold extraction.…”
Section: Mechanism Study Of Rgo's Gold Extraction Behaviormentioning
confidence: 99%
“…In comparison to the reported novel gold adsorbents, though some showed reductive adsorption, other physi-and chemi-sorptions were also significant. That is, gold extracted by these adsorbents was a mixture of ionic and metallic gold 4,[12][13][14][15]19,[27][28][29] , therefore, it would require energy-and cost-intensive post-processing, for example, elution and precipitation to desorb and reduce the ionic gold, so that a full adsorption capacity can be achieved 30,31 . In contrast, as >95% extracted Au ions were reduced to metallic gold by rGO, it allowed direct isolation of metallic gold from rGO surface without further post-adsorption processing, providing an extra advantage of rGO for gold extraction.…”
Section: Mechanism Study Of Rgo's Gold Extraction Behaviormentioning
confidence: 99%
“…Various kinds of metal–organic frameworks (MOFs) and covalent organic frameworks (COFs) were also exploited in gold capture from aqueous solutions [9–11] . The simple pyridine‐carboxylic acid, niacin was also used to precipitate gold halides selectively from mixed‐metal acidic solutions [12] . Love and co‐workers developed a simple primary amide and showed that gold was recovered selectively from a mixture of metals representative of e‐waste by solvent extraction [13] .…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 , 10 , 11 ] The simple pyridine‐carboxylic acid, niacin was also used to precipitate gold halides selectively from mixed‐metal acidic solutions. [12] Love and co‐workers developed a simple primary amide and showed that gold was recovered selectively from a mixture of metals representative of e‐waste by solvent extraction. [13] Following on from this work, a method was developed for the selective precipitation of Au and Pt using a simple diamide.…”
Section: Introductionmentioning
confidence: 99%
“…Supramolecular interactions between acyclic durene diamides and HAuCl 4 resulted in gold precipitation as extended networks, although in these cases no selectivity for gold over other metals was explored 32 . Extended supramolecular network structures were also formed upon selective precipitation of HAuCl 4 from acidic solutions comprising Au, Ni, Cu, Zn, alkali-, and alkaline-earth metals by the biomolecule niacin, a pyridine carboxylic acid 33 .…”
Section: Introductionmentioning
confidence: 99%